Co-Creation dalam Pendampingan Guru: Desain Manajemen Pembelajaran P5-PPRA Berbasis Moderasi Beragama - Abu Choir; Muhammad Shobirin; Muhammad Syamsu Dhuha (Universitas Nurul Jadid, 2026)
This community service activity was motivated by the suboptimal implementation of the Projek Penguatan Profil Pelajar Pancasila dan Rahmatan lil ‘Alamin (P5-PPRA) at MI Alam Alfa Kids. Although teachers have implemented character projects, the teaching modules have not been systematically developed based on developmental phases, the indicators for attitude evaluation remain unmeasured, and the integration of religious moderation values is still largely normative. In addition, limited time and the absence of a structured project management model have resulted in inconsistent implementation. This program aimed to design and implement a collaborative learning management model for P5-PPRA based on religious moderation. The method used was Participatory Action Research (PAR) with the principles of co-creation, co-collaboration, and co-evaluation through Focus Group Discussions (FGD), mentoring in module development, implementation based on the PKART flow, and joint reflective evaluation. The local wisdom integrated into the program was the interfaith harmony practices in Dukuh Pekoso Kidulan, Tempur Village, Jepara, characterized by the presence of a mosque and a church located side by side and traditions of mutual cooperation among religious communities as contextual learning resources. The results show the development of phase-based teaching modules integrated with measurable character indicators, improved teacher capacity in designing authentic assessments, and an increase in students’ collaboration and reflection scores from 2.8 to 3.5 (scale of 4). These findings indicate that participatory and reflective learning management based on religious moderation can strengthen contextual and sustainable character education practices in Islamic elementary schools.